Marketing Strategy And Innovation To Enhance Msmes Marketing Performance: Competitive Advantage As Intervening Variable - Asaroh, Laily Khomsyata; Komariyatin, Nurul (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to analyze the effects of creativity in marketing strategies and product innovation on the marketing performance of furniture micro, small, and medium enterprises (MSMEs) in Jepara, with competitive advantage as an intervening variable. Utilizing a quantitative approach, data were collected from 150 MSMEs through questionnaires and subsequently analyzed using the Structural Equation Modeling method with SmartPLS 4.0. The results indicate that creativity in marketing strategies has a significant impact on both competitive advantage and marketing performance, whereas product innovation exhibits a significant effect solely on marketing performance and not on competitive advantage. This finding suggests that competitive advantage plays a significant mediating role in the relationship between creativity in marketing strategies and marketing performance. The lack of a significant effect of product innovation on competitive advantage is believed to be influenced by the homogeneity of product design and consumer perceptions that prioritize traditional elements. Consequently, MSMEs are encouraged to develop creative marketing strategies and product differentiation that align with market values to enhance their competitiveness and improve marketing performance.